Growth and Yields of Upland Rice (Oryza sativa L.) Applied by Synthetic Zeolite and Catfish Liquid Organic Fertilizer - Mutiara Putri; Nelvia Nelvia (JOURNAL OF TROPICAL SOILS, 2023)
The average productivity of upland rice in Indonesia is around 4.4 tons per ha, significantly lower than its potential yield of 8.5 Mg per ha. The utilization of synthetic zeolite as a soil amendment and liquid organic fertilizer (LOF) is one of the technologies that can be applied to increase the growth and yield of upland rice. This study was carried out by factorial experiment with 2 factors: synthetic zeolite application at 4 levels (0, 100, 150, and 200 kg per ha), and catfish LOF application at 3 levels (0, 200, and 400 ml per clump), and each combina- tion was repeated three times. The results showed that applying synthetic zeolite and catfish LOF at each dose had no significant effect on plant height, maximum number of tillers and productive tillers, panicle exit age, harvest age, and weight of milled dry grain per clump. The interaction of synthetic zeolite at a dose of 100 kg per ha with catfish LOF at a dose of 400 ml per clump increased the number of pithy grains per panicle by 70%, the weight of milled dry grain per clump by 68%, and the harvest index 37.5% significantly compared to control (no treatment).